Development of internet toolkit for computer engineering courses - Chasqueira, Hugo (2020)
Recent growth in the WWW (Word Wide Web) and Java has received significant attention as means to share sophisticated and expensive laboratory equipment in Computer Engineering Courses. To share a Digital Pendulum System in class laboratory and with other educational institutions, this paper proposes an Internet Toolkit for Computer Engineering Courses. This allows the monitoring and experiment of a Digital Pendulum System from remote place. A simple and easy-to-use Web interface was developed to help students, and other users, in lab experiences using default control algorithms.